Entrance of the Neelkanth Mahadev Temple as seen from the interior - Temples of India Project Team (Jio Institute, 2024)
This is a view of the entrance of the Neelkanth Mahadev Temple as seen from the interior of the temple. The west-facing entrance leads into a mandapa (pillared hall), which is attached to three shrines.